2018
DOI: 10.21608/jssae.2018.36474
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing of Using Potassium Fertilizer by Using Foliar Spraying and Organic Manuring and Its Effect on Maize Productivity and Soil Properties

Abstract: Two field experiments were performed in the Agricultural Farm of Sids Agricultural Research Station, ARC, Beni-Suef Governorate during two seasons of 2016 and 2017 to evaluate using foliar spraying of 2% mono-potassium sulphate or di-potassium sulphate twice for minimizing the use of chemical potassium fertilizer (0.0, 50 and 100 kg K 2 SO 4 /fed) under different doses of organic manure (0.0, 2.5 and 5 t/fed chicken manure)and its effect on maize productivity, namely, growth parameters (plant height and dry we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In this connection, Saison et al (2006) reported that compost is often viewed as a way to improving soil fertilizer by improving soil physical properties as well as increasing soil organic carbon and nutrient availability. Similar results were obtained by El-Sheref et al (2018). This may be due to the decomposition of organic manure which supplied more available nutrient elements and formation of organic and inorganic acids during decomposition which slightly reduced the soil pH which affected the solubility and availability of N, P and K. These beneficial effects were also reported by El-Kouny (2007).…”
Section: Soil Fertilitysupporting
confidence: 83%
“…In this connection, Saison et al (2006) reported that compost is often viewed as a way to improving soil fertilizer by improving soil physical properties as well as increasing soil organic carbon and nutrient availability. Similar results were obtained by El-Sheref et al (2018). This may be due to the decomposition of organic manure which supplied more available nutrient elements and formation of organic and inorganic acids during decomposition which slightly reduced the soil pH which affected the solubility and availability of N, P and K. These beneficial effects were also reported by El-Kouny (2007).…”
Section: Soil Fertilitysupporting
confidence: 83%